California Elected Women's Association for Education and Research Newsletter (1977)
This June 1977 newsletter of the California Elected Women's Association for Education and Research (CEWAER) highlights the organization's role in supporting women transitioning into higher public office, including a testimonial from Sonoma County Supervisor Helen Rudee describing CEWAER as a vital resource network. It introduces the 1977–78 board and nominees, outlines action priorities such as affirmative action, housing for homeless women, policy influence, and development of statewide information networks, and reports on recent events including the Coronado conference. The newsletter also announces upcoming meetings, promotes regional growth, and invites membership participation to strengthen support for elected women across California.